PEMBELAJARAN BACA TULIS AL-QURAN (BTQ) DI SMA ISLAM TAWASALNA DALAM MENINGKATKAN KEMAMPUAN MEMBACA Al-QUR’AN - Husen, Mochamad (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2023)
The aim of the research is to dig deeper into the ability of students at Tawasalna Islamic High School in reading the Koran, the effectiveness of BTQ learning, the BTQ learning process on the ability to read Al-Quran surah Al-Baqarah. This study uses a case study method with a qualitative research approach, data sources are BTQ Teachers and Students, data collection techniques use observation, interviews and documentation, data analysis is by data reduction, data presentation and drawing conclusions. The results of the research on the ability of students at Tawasalna Islamic High School in reading the Koran from four students, three of whom are already able to read the Koran and one of them has not been able to read the Koran, 2) Learning Process by listening to the reading, repeating reading , and use the Asyarah method.